(untitled) (Colombia Medica, 2024)
Background Sinonasal lesions are common benign masses with overlapping clinical and histopathological features. Extracellular matrix proteins such as periostin, fibronectin, and tenascin-C play key roles in tissue remodeling and inflammation, yet their distinct expression profiles in these lesions remain poorly defined. Aim This study aimed to compare the immunohistochemical staining patterns of periostin, fibronectin, and tenascin-C in sinonasal lesions to elucidate their roles in pathogenesis and enhance differential diagnosis. Methods In this retrospective study, pathological specimens from 70 patients who underwent surgery for sinonasal polyps were analyzed. Using a semi-quantitative scoring system, the immunohistochemical expression of periostin, fibronectin, and tenascin-C was assessed separately in epithelial and stromal compartments. Multinomial logistic regression analysis evaluated associations between staining patterns and lesion types. Results The study cohort had a male-to-female ratio of 5:2 with a mean age of approximately 40. Nasal polyps demonstrated significantly higher stromal periostin staining than antrochoanal polyps and inverted papillomas. Conversely, antrochoanal polyps exhibited significantly elevated epithelial periostin expression relative to inverted papillomas. Fibronectin expression was markedly increased in nasal polyps, particularly within the stroma, supporting its role in inflammatory tissue remodeling. In contrast, tenascin-C did not display significant differences among the lesion types. Conclusion The differential expression of periostin and fibronectin in sinonasal lesions underscores distinct pathogenic mechanisms that may aid in more accurate diagnosis. The compartment-specific staining patterns of periostin and the prominent fibronectin expression in nasal polyps suggest these biomarkers could serve as valuable diagnostic tools and potential therapeutic targets. Future studies should further explore these pathways to develop targeted interventions for sinonasal diseases.